Genetic association-based functional analysis detects HOGA1 as a potential gene involved in fat accumulation - Kim, Myungsuk; Park, Kye Won; Ahn, Yeongseon; Lim, Eun Bi; Kwak, Soo Heon; Randy, Ahmad; Song, No Joon; Park, Kyong Soo; Nho, Chu Won; Cho, Yoon Shin (Frontiers in Genetics, 2022)
Although there are a number of discoveries from genome-wide association studies (GWAS) for obesity, the success of linking GWAS results to biology is lacking. We sought to discover causal genes for obesity by conducting functional studies on genes detected from genetic association analysis. Gene-based association analysis of 917 individual exome sequences showed that HOGA1 attains exome-wide significance (P-value < 2.7 × 10-6) for body mass index (BMI). There is a significant increasd the mRNA expression of HOGA1 in human adipose tissues from obese individuals in the Genotype-Tissue Expression (GTEx) dataset which supports the genetic association of HOGA1 with BMI. Functional analyses employing cell- and animal model-based approaches was performed to gain insight into the functional relevance of HOGA1 to obesity. Adipogenesis was retarded when Hoga1 was knocked down by siRNA treatment in a mouse 3T3-L1 cell line and a similar inhibitory effect was confirmed in mice with down-regulated Hoga1. Hoga1 siRNA treatment reduced body weight, blood lipid level, blood glucose, and adipocyte size in high-fat diet-induced mice. In addition, several lipogenic genes including Srebf1, Scd1, Lp1, and Acaca were down-regulated, while lipolytic genes Cpt1l, Ppara, and Ucp1 were up-regulated. Taken together, HOGA1 is a potential causal gene for obesity by playing a role in excess body fat development.